Impact of Exchange Stay on Alcohol Consumption: Longitudinal Exploration in a Large Sample of European Students. (29th April 2019) - Dormal, Valérie; Lannoy, Séverine; Maurage, Pierre
Abstract : Background: Each year, more than 300, 000 university students take part in European exchange programs. Besides their positive educational and cultural impacts, these programs are also reputed to immerse students in a high‐risk festive context where excessive alcohol consumption is strongly present. There is thus a crucial need to evaluate the actual impact of those exchange stays on alcohol consumption. Methods: Study abroad ( n = 3, 950) and local ( n = 3, 950) European students completed a 2‐part longitudinal survey and reported their alcohol consumption before (T1) and during (T2) their exchange stay (or at the beginning of the academic year and 6 months later for local students, constituting the control group). Results: During their exchange stay, individuals studying abroad showed more excessive and harmful alcohol consumption behaviors than local students, as measured by increased general alcohol consumption and binge drinking (BD) scores at T2. In particular, study abroad students under 20 years of age and performing their exchange stay in eastern Europe were the most exposed to excessive alcohol consumption and BD. Conclusions: These results constitute the first large‐scale longitudinal confirmation that exchange stays indeed constitute risky contexts in which students significantly increase their consumption and present stronger alcohol‐related problems. In view of the rapid and deleterious effects of alcohol consumption in young people, it is essential to promote prevention campaigns targeting this population to limit public health consequences and possible evolution toward severe alcohol use disorders. Abstract : Many students go abroad during their University studies, leading to personal and academic opportunities but also to increased alcohol consumption risk. In a European study comparing large samples of study abroad students with matched students staying home, we showed that the frequency and intensity of excessive consumption episodes (and specifically of binge drinking) increased during stays abroad, particularly among younger students. Alcohol prevention programs targeting students before and during these stays should be encouraged to protect their health and well being.